Evolution of implanted Fe ions in SiO2/Si wafer into uniformly sized catalyst particles for carbon nanotube forest growth. (October 2017) - Lee, Cheol-Hun; Lee, Jaegeun; Yeo, Sunmog; Lee, Sung-Hyun; Kim, Teawon; Cha, Hyeon-Gu; Eun, Youngmoo; Park, Hyun Jin; Kim, Seung Min; Lee, Kun-Hong
Abstract: We report the synthesis of carbon nanotube (CNT) forests with a narrow diameter distribution based on Fe ion implantation method. By annealing the Fe-implanted SiO2 /Si wafer in an Ar atmosphere at 800 °C for 15 min, the Fe particles on the surface of SiO2 layer are successfully formed by the diffusion of Fe atoms from the SiO2 layer. Interestingly, the size distribution of Fe catalyst particles for Fe-implanted SiO2 /Si wafers does not change with the prolonged annealing durations of up to 12 h. Using secondary ion mass spectroscopy and transmission electron microscopy (TEM), we confirmed that the implanted Fe atoms diffuse out of the SiO2 layer and form Fe particles on both the SiO2 surface and the interface between SiO2 and Si. The cross-sectional TEM images indicate that the Fe catalyst particles are anchored in the SiO2 layer, which limits the particles' mobility and results in an invariant catalyst size distribution for prolonged annealing durations. Therefore, we anticipate that implantation can be an efficient alternative catalyst preparation method for CNT forest growth which can solve various growth issues that are inherently caused by conventional physical vapor deposition method. Graphical abstract: